Chapter Giordano da Pisa e il pubblico. Modelli e comportamenti - IANNELLA, CECILIA (Reti Medievali E-Book, 2020)
The production of Giordano da Pisa (1260-1310) offers an excellent example for assessing the relationship between a Dominican preacher and his lay audience. His preaching presents simultaneously all the features that make it possible to regard it as a document of how the preacher and the public may have influenced each other. This paper illustrates how the friar proposes a social model and individual behaviours in the relationship between the ideal world and reality.